Pembangunan Sistem Informasi Institusi Medis Uniq Kidz Nusantara - NUGRAHA, RADITYA YOGA; Sinaga, Benyamin Langgu; Suyoto (Universitas Atma Jaya Yogyakarta, 2025)
School for children with special needs was established to assist the community in educating and supporting children with special needs. Operational difficulties in this institution are caused by operational data which still recorded manually. Another problem faced is the difficulty in maintaining data integrity due to data loss. Based on the issues above, a web-based information system (SIUNIK) was developed for the staff of Uniq Kids Nusantara to assist in the institution’s operational processes. It was developed using the PHP frameworks: Laravel and Filament; and SQLite database. Based on the research results, it can be concluded that the SIUNIK information system was successfully developed. This system can assist the institution’s operations. Based on system testing, an average effectiveness score of 4.63 was achieved. From the testing results, it can be concluded that this information system can support both the operational processes and data integrity of Uniq Kidz Nusantara. Sekolah untuk anak berkebutuhan khusus didirikan untuk membantu masyarakat dalam mendidik dan mendukung anak berkebutuhan khusus. Kendala operasional di lembaga ini disebabkan oleh data operasional yang masih tercatat secara manual. Masalah lain yang dihadapi adalah kesulitan dalam menjaga integritas data karena kehilangan data. Berdasarkan permasalahan di atas, sistem informasi berbasis web (SIUNIK) dikembangkan untuk staf Uniq Kids Nusantara untuk membantu proses operasional lembaga. Sistem ini dikembangkan menggunakan kerangka kerja PHP: Laravel dan Filament; dan basis data SQLite. Berdasarkan hasil penelitian, dapat disimpulkan bahwa sistem informasi SIUNIK berhasil dikembangkan. Sistem ini dapat membantu operasional lembaga. Berdasarkan pengujian sistem, skor efektivitas rata-rata sebesar 4,63 dicapai. Dari hasil pengujian, dapat disimpulkan bahwa sistem informasi ini dapat mendukung proses operasional dan integritas data Uniq Kidz Nusantara.